Electrochemical and Structural Studies of LiNi0.85Co0.1Mn0.05O2, a Cathode Material for High Energy Density Li-Ion Batteries, Stabilized by Doping with Small Amounts of Tungsten. Issue 6 (25th June 2021) - Levartovsky, Yehonatan; Kunnikuruvan, Sooraj; Chakraborty, Arup; Maiti, Sandipan; Grinblat, Judith; Talianker, Michael; Major, Dan Thomas; Aurbach, Doron
Abstract : The specific capacity of Ni rich LiNi x Co y Mn z O 2 x > 0.5 ) cathodes is higher as their Ni content is higher and can reach values up to 240 mAh g −1 (x →1) while being charged below 4.3 V vs Li. This property is very important since charging Li-ion batteries below this potential is not detrimental to anodic stability of the electrolyte solution. However, as the content of Ni increases, the electrochemical, structural and thermal stability decreases. Here we focus on LiNi 0.85 Co 0.1 Mn 0.05 O 2 which was stabilized by doping it with W by a simple solid-state method. This doping greatly improved the electrochemical, thermal and structural stability, although both X-ray diffraction and density functional theory (DFT) studies indicated negligible change in the structural parameters upon doping. For example, 96% capacity retention was achieved for doped cathodes after 120 cycles at 45 °C vs Li anodes, compared to 80% capacity retention for an undoped, reference cathode. Cross sectioning studies of cycled cathodes by SEM imaging of FIB-cut samples confirmed the correlation between structural and electrochemical stability. W-doping stabilizes the cathode material by reducing the formation of cracks and loss of the spherical shape of the active mass particles, upon prolonged cycling. Additionally, W-doping enhances the thermal stability of the cathode material. DFT based calculations indicated that doping this cathode material with tungsten, reduces the amount of Jahn-Teller active Ni 3+ ions within the crystal lattice and introduces strong W-O bonds, which stabilize the active mass during repeated lithiation—lithiation cycling.